Negative Impact of Artificial Intelligence in the World of Image-based Editing - Adelia Nur Fitriana; Vina Salima Mujahida; Ali Zainal Abidin; Ahmad Naufal; Muhammad Rizal Rafli (Penerbit Hellow Pustaka, 2024)
Recently, artificial intelligence technology has been talked about by young people. Artificial intelligence is one of the developments in the digital era like this. This AI is artificial intelligence made by humans. AI is a branch of computer science. Over time, AI technology has played certain tasks and roles in everyday life, especially in the business world. It can be concluded that artificial intelligence, or artificial intelligence, learns from human experience to do human tasks in general. In the development of the world in this digital era, there are many crimes that are rampant. There is one AI technology that is used for crimes, for example, deepfake.